Neurology (Advanstar Communications, 1951)
As the leading clinical neurology journal worldwide, Neurology is directed to physicians concerned with diseases and conditions of the nervous system. The journal's purpose is to advance the field by presenting new basic and clinical research with emphasis on knowledge that will influence the way neurology is practiced. The journal is at the forefront in disseminating cutting-edge, peer-reviewed information to the neurology community worldwide.
Keywords: neurologie; Neurology